Solve the simultaneous equations: (a) y - 2x = 6; (b) y+2x = 0.

  • rearrange equation (a) to be: y = 6 + 2x. Substitute this into equation (b) to get: (6 + 2x) + 2x = 0

  • rearrange this to get: 6 + 4x = 0. Simplify to get x = -(6/4). Get the value for x to be: x = -1.5.

  • substitute this x value into equation (b) to get the value for y, hence we get: y + 2(-1.5) = 0; y = 3.

Answered by Faizan M. Maths tutor

9637 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

What are surds and how does multiplying them work?


Expand and simplify 2(a + 3) + 5(a – 1)


The equation of Line 1 is y= 3x-2, and the equation of Line 2 is 5= 9x- 3y. Are the two lines parallel?


Calculate the length of PR. Give your answer correct to 3 significant figures (Diagram displayed on whiteboard)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences